Tingkat Stres Dosen Perempuan UII Ditinjau Dari Dukungan Suami - Retno Kumolohadi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2001)
This research aimed to examine  the  relationship between level of stress and social support from husba.nd The hypothesis was tested there was a negative coreteuon  between level of stress and social support from husband.The subjects of this research were 30 women lecturer from Islamic Unntersity of Indonesia.  The data collection was done using the quetionaire method for the  scale of stress and social support from husband.The refationship between level of stress and social support from hus band used by product moment analysis.   The result ofcorreteuon analysis was r"" -.558; p = 0.001  (one  tailed  analysis) This means that the higher social support from husband,  the lower level of stress. Social support from husband give 31, 17 % contribution. Level of stress women lecturer of Islamic university of Indonesia is lowest. Social support from her husband is highest. Kata Kunci: stress lecturer woman, social support from  husband